Legal Aid Post Services at the Indonesian Religious Courts during the COVID-19 Pandemic - Ramdani Wahyu Sururie; Yoghi Arief Susanto (Universitas Islam Negeri Jakarta, 2020)
The spread of the Corona Virus Disease 2019 (COVID-19) has been declared as a health and economic emergency that has an impact on social life, including Legal Aid Post services at the Indonesian Religious Courts. This study aims to analyze the types, forms, and methods of Legal Aid Post services at the Religious Courts and the level of public access to the Religious Courts during the COVID-19 pandemic. This research uses an empirical juridical method with a qualitative approach. Descriptive and exploratory analysis are carried out to identify Legal Aid Post services at the Religious Courts in providing judicial access to the public. This study also uses purposive sampling before conducting in-depth interviews with several informants. These include Religious Court employees, advocates, and Legal Aid Post officers. The results show that the case registration services at the Legal Aid Post for the Religious Courts have been carried out in various forms, namely online through the E-Court application and manually by visiting the Religious Court. Thus, this study shows that Legal Aid Post services at the Indonesian Religious Courts during the COVID-19 pandemic have been carried out differently in various Religious Courts. AbstrakPenyebaran COVID-19 telah ditetapkan sebagai darurat kesehatan dan ekonomi yang berdampak pada kehidupan sosial, termasuk pelayanan posko bantuan hukum di Pengadilan Agama. Penelitian ini bertujuan untuk menganalisis jenis, bentuk, dan metode pelayanan Pos Bantuan Hukum di Peradilan Agama serta tingkat akses masyarakat terhadap Peradilan Agama selama periode COVID-19. Penelitian ini menggunakan metode yuridis empiris dengan pendekatan kualitatif. Analisis deskriptif dan eksploratif dilakukan untuk mengidentifikasi layanan Pos Bantuan Hukum di Pengadilan Agama dalam memberikan akses peradilan kepada publik. Penelitian ini juga menggunakan purposive sampling sebelum melakukan wawancara mendalam dengan beberapa informan, termasuk pegawai pengadilan agama, advokat, dan petugas Pos Bantuan Hukum. Hasil penelitian menunjukkan bahwa pelayanan pencatatan perkara di Pos Bantuan Hukum Pengadilan Agama telah dilakukan dalam berbagai bentuk yaitu secara online melalui aplikasi E-Court dan secara manual dengan mengunjungi Pengadilan Agama. Terkait tingkat akses, masyarakat yang mengakses Pengadilan Agama saat pandemi COVID-19 mengalami penurunan. Dengan demikian, penelitian ini menunjukkan bahwa pelayanan Pos Bantuan Hukum di Pengadilan Agama selama periode COVID-19 telah dilakukan secara berbeda di berbagai Pengadilan Agama.